Bogowie jak ludzie. Ludzkie cechy i umiejętności bogów starożytnego Bliskiego Wschodu. Część II - Sieradzan, Jacek (Humaniora. Czasopismo Internetowe, 2022)
Biblical texts attribute the same activities and features to biblical gods Yahweh and Jesus, as other – and mostly older – texts of Ancient Near East attribute to other gods. Almost all features and activities of non-biblical gods have been transfered to biblical gods. It means that Ancient Near East religious thinkers shared mostly common worldview. Our analysis undermines opinion of uniqueness of Judaism and Christianity. Such view is false, it is creation of Jewish and Christian theologians. One cannot find supprot to the view in written sources.